State’s Loses in The Corruption Crimes of Members of The Board of Directors of State-Owned (Persero) or Regional Government-Owned Banks and Their Subsidiaries in The Provision of Credit/ Financing - Try Widiyono; Farhana Farhana (Law and Human Rights Policy Strategy Agency, Ministry of Law and Human Rights of The Repub, 2022)
Law No. 31 of 1999 as amended by Law No. 20 of 2001 on Eradication of Corruption Crimes provides normative direction that one of the essential things that must be proven in corruption crime is the existence of “State’s losses”. Members of the Board of Directors of State-Owned Enterprise in the form of bank, in managing of the company, especially in the provision of credit or financing, are very afraid of being accused of corruption crimes. The legal relationship between the State as a legal subject with the companies having status as State-Owned Enterprises (the Persero) is the existence of majority share ownership or controlling shares by the State in limited liability companies with Persero status. Such a legal relationship has been regulated in various applicable laws and regulations that have and are sourced from theoretical and philosophical foundations such as corporate legal doctrines for example the legal doctrine of piercing the corporate veil, the doctrine of fiduciary duty law, and the Business Judgment role. Some legal problems arise, namely how is the legal relationship of the State with State Enterprises? And can the non-performing credit or non-performing bank financing affect the value of the State’s participation in State-owned Bank /Region-Owned Bank? The legal research used in addressing the issues in question is normative legal research, and therefore the results obtained in this legal research are what they should be.